Pengaruh Penggunaan Media Benda Asli Terhadap Prestasi Belajar pada Mata Pelajaran IPA Kelas III Sekolah Dasar Negeri No. 6 Pinrang Kabupaten Pinrang - Agustina (Science Education and Learning Journal, 2021)
This research is a type of experimental research conducted at SD No. 6 Pinrang with the aim of getting an overview of students' ability to use real object media as learning media in biology science subjects in class III. The population of this study were all thirdgrade students, totaling 34 people. Because the population is relatively small, the researchers used a population sample. The population sample was randomized to be divided into two research objects, namely the experimental group and the control group. the experimental group is a group of students who are taught using real object media and the control group is a group of students who are taught without using real object media. Data collection was taken through documentation techniques, experimental techniques, and test techniques and then analyzed statistically using mean analysis. The results of this study illustrate the effect of increasing the writing ability of students who are taught by using serial image media compared to students who are taught without using serial image media, namely 21.4 > 20.4. This research is expected to contribute ideas to the utilization of serial image media in the teaching and learning process to improve students' ability to use real object media.